Drug Delivery Systems - Jain, Kewal K.; Jain, Kewal K. (Methods in Molecular Biology,, 2008)
The field of drug development and therapeutics can be overwhelmingly encyclopedic and vast. In Drug Delivery Systems, Dr. Kewal Jain and a team of experts select the most important, cutting-edge technologies used in drug delivery systems taking into account significant drugs, new technologies such as nanoparticles, and therapeutic applications. The chapters present step-by-step laboratory protocols following the highly successful Methods in Molecular Biology™ series format, offering readily reproducible results vital for pharmaceutical physicians and scientists. Concise and systematic, Drug Delivery Systems is a powerful reference tool for the hundreds of companies developing drug delivery technologies all around the world.